Macro Policy and Employment Problems in Latin America - Eduardo Lora; Mauricio Olivera (Inter-American Development Bank, Office of the Chief Economist, 1998)
This paper was prepared for the 1998 IDB/IIC Annual Meeting entitled: The Employment in Latin America: What is the Problem and Should it be Addressed? held in Cartagena, Colombia in March 1998. Despite macroeconomic stabilization and structural reforms, employment problems have persisted in Latin America. The 1990s have seen a slowdown in the rate of job creation, and unemployment rates have stagnated at about 10 percent. Informal sector employment has expanded, and increases in real wages have been particularly favorable to skilled workers. Economic cycles explain fluctuations in the employment and unemployment rates, while price stabilization and structural reforms have affected the composition of labor demand and relative wages.
Keywords: 330; Erwerbstätigkeit; Arbeitslosigkeit; Konjunkturpolitik; Wirtschaftsreform; Arbeitsnachfrage; Lateinamerika